Risk of Epilepsy After Complex Febrile Seizures - J Gordon Millichap (Pediatric Neurology Briefs, 2001)
The risk of epilepsy developing after complex febrile seizures (CFS) was studied in 477 children admitted between 1991 and 1998 with febrile convulsions at Tel Aviv Medical Center, Israel.